2013
DOI: 10.1007/s11999-013-2897-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Botulinum Toxin A Injections into the Calf Muscles on Genu Recurvatum in Children With Cerebral Palsy

Abstract: Background With cerebral palsy (CP), an equinus deformity may lead to genu recurvatum. Botulinum toxin A (BtA) injection into the calf muscles is a well-accepted treatment for dynamic equinus deformity. Questions/purposes The purpose of this study was to determine whether BtA injections into the calf muscles to decrease equinus would decrease coexisting genu recurvatum in children with diplegic CP. Methods In a retrospective study, 13 children (mean age, 5 years) with spastic diplegic CP showing equinus and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…A number of studies have demonstrated the benefits of BoNT-A injection for dynamic equinus foot in patients with CP. 1 2 13 14 15 19 34 35 However, previous studies on the effects of such an injection for dynamic equinovarus foot have rarely addressed children with CP. For dynamic equinovarus foot, TP and calf muscles are the target muscles for BoNT-A injection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies have demonstrated the benefits of BoNT-A injection for dynamic equinus foot in patients with CP. 1 2 13 14 15 19 34 35 However, previous studies on the effects of such an injection for dynamic equinovarus foot have rarely addressed children with CP. For dynamic equinovarus foot, TP and calf muscles are the target muscles for BoNT-A injection.…”
Section: Discussionmentioning
confidence: 99%
“…In children with CP with dynamic equinus foot, a number of studies have previously demonstrated significant improvements in ankle kinematic parameters 10 11 12 13 15 39 and kinetic data 10 12 using computerized gait analysis after BoNT-A injection into the calf muscles. The significant improvements in ankle kinematic data shown in our study were due to the reduction of ankle plantarflexor tone after injection, which contributed to significant improvement in ankle dorsiflexion during gait.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations